A thermoresponsive polymer supporter for concerted catalysis of ferrocene with a ruthenium catalyst in living radical polymerization: high activity and efficient removal of metal residues. Issue 45 (14th October 2015) - Fujimura, Kojiro; Ouchi, Makoto; Sawamoto, Mitsuo
Abstract : A thermoresponsive polymer-supported catalyst consisting of a ruthenium (Ru) main catalyst and a ferrocene (Fc) cocatalyst was designed to realize both high activity and efficient removal of metal residues. Abstract : A thermoresponsive polymer-supported catalyst consisting of a ruthenium (Ru) main catalyst and a ferrocene (Fc) cocatalyst was designed to realize both high activity and efficient removal of metal residues. The supported catalyst/cocatalyst was easily prepared via ternary random free radical copolymerization of vinylferrocene (VFc), phosphine-pendant monomer (SDP), and PEG-pendant methacrylate (PEGMA), followed by mixing with a Ru precursor ([Ru(Cp*)Cl]4 ). The thermoresponsive feature was confirmed by visual appearance with a water/toluene binary solvent: it was preferably soluble in water at room temperature but moved to the toluene phase at high temperature for polymerization. The supported catalyst/cocatalyst showed high catalytic activity for living radical polymerization of MMA in toluene to give controlled PMMAs with narrow molecular weight distributions and a high halogen end functionality ( e.g., M w / M n = 1.16 and 96% Cl-end of PMMA obtained at 89% conversion in 24 h). The metal residues in PMMA can almost be quantitatively removed via water washing of the resulting polymerization solution [Residual Ru: 5.7 ppm (99.8% removal), residual Fe: 89 ppm (98.5% removal), characterized by ICP-AES analysis].